An Evaluation of an Inductively Coupled Plasma (ICP) Emission Spectrometer - Lee, Chnoong Kheng; Hoh, R.; Low, Kun She (1982)
The performance of an Inductively Coupled Plasma (ICP) emission spectrometer was evaluated in' terms of its monochromator resettability, ICP generator stability and detection limits. The studies showed that the analytical system exhibited similar performance to simultaneous direct reading spectrometers. The reliability of the monochromator, torch heigh t adjustor and the stability of the source unit were confirmed.